An inflammatory paradox: strategies inflammophilic oral pathobionts employ to exploit innate immunity via neutrophil manipulation - Higashi, Dustin L.; Qin, Hua; Borland, Christina; Kreth, Jens; Merritt, Justin (Frontiers in Oral Health, 2024)
Inflammatory dysbiotic diseases present an intriguing biological paradox. Like most other infectious disease processes, the alarm bells of the host are potently activated by tissue-destructive pathobionts, triggering a cascade of physiological responses that ultimately mobilize immune cells like neutrophils to sites of active infection. Typically, these inflammatory host responses are critical to inhibit and/or eradicate infecting microbes. However, for many inflammatory dysbiotic diseases, inflammophilic pathobiont-enriched communities not only survive the inflammatory response, but they actually obtain a growth advantage when challenged with an inflammatory environment. This is especially true for those organisms that have evolved various strategies to resist and/or manipulate components of innate immunity. In contrast, members of the commensal microbiome typically experience a competitive growth disadvantage under inflammatory selective pressure, hindering their critical ability to restrict pathobiont proliferation. Here, we examine examples of bacteria-neutrophil interactions from both conventional pathogens and inflammophiles. We discuss some of the strategies utilized by them to illustrate how inflammophilic microbes can play a central role in the positive feedback cycle that exemplifies dysbiotic chronic inflammatory diseases.